Polysaccharide structures and interactions in a lithium chloride/urea/water solvent - Winkworth-Smith, Charles G.; Macnaughtan, William; Foster, Tim (Elsevier, 2016)
The molten salt hydrate, lithium chloride (LiCl)/urea/water has previously been shown to swell cellulose, but there has so far been no work done to explore its effect on other polysaccharides. In this paper we have investigated the solvent effects of LiCl/urea/water on four natural polysaccharides. Fenugreek gum and xyloglucan, which are both highly branched, were found to increase in viscosity in LiCl/urea/water relative to water, possibly due to the breakage of all intra-molecular associations whereas the viscosity of konjac glucomannan which is predominantly unbranched did not change. Locust bean gum (LBG) had a lower viscosity in LiCl/urea/water compared to water due to the disruption of aggregates. Confocal microscopy showed that fenugreek gum and LBG are able to bind to cellulose in water, however, the conformational change of fenugreek gum in these solvent conditions inhibited it from binding to cellulose in LiCl/urea/water whereas conformational change allowed xyloglucan to bind to cellulose in LiCl/urea/water whilst it was unable to bind in water. Konjac glucomannan did not bind to cellulose in either solvent system. These results provide new insights into the impact of polysaccharide fine structure on conformational change in different solvent environments.